2007
DOI: 10.1093/jn/137.12.2653
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Levels of Vitamin E and Carotenoids Are Associated with Genetic Polymorphisms in Genes Involved in Lipid Metabolism , ,3

Abstract: Vitamin E and carotenoids are fat-soluble micronutrients carried by plasma lipoproteins. Their plasma concentrations are governed by several factors, some of which are genetic, but data on these genetic factors remain scarce. We hypothesized that genes involved in lipid metabolism, i.e. the genes implicated in intestinal uptake, intracellular trafficking, and the lipoprotein distribution of lipids, play a role in the plasma concentrations of these micronutrients. To verify this hypothesis, we assessed whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 32 publications
9
123
1
4
Order By: Relevance
“…Vitamin E metabolism protein (i.e., A395V, G402S, R417W, and G434R) showed lower transport efficiencies for both cholesterol and α-TOH [216] . Borel et al [217] analyzed polymorphisms in genes involved in lipid metabolism, namely APOA4, APOB, APOE, LPL and SRBI, and found α-or γ-TOH levels to be different in subjects with SNPs in APO4, APOE and SRBI or APO4 and SRBI, respectively. Major et al [218] found three SNPs to be associated with circulating α-TOH serum levels, rs964184 near APOA1, APOA4, APOA5 and APOC3, rs2108622 in CYP4F2 as well as rs11057830 in SCARB1.…”
Section: Genetic Polymorphismsmentioning
confidence: 99%
“…Vitamin E metabolism protein (i.e., A395V, G402S, R417W, and G434R) showed lower transport efficiencies for both cholesterol and α-TOH [216] . Borel et al [217] analyzed polymorphisms in genes involved in lipid metabolism, namely APOA4, APOB, APOE, LPL and SRBI, and found α-or γ-TOH levels to be different in subjects with SNPs in APO4, APOE and SRBI or APO4 and SRBI, respectively. Major et al [218] found three SNPs to be associated with circulating α-TOH serum levels, rs964184 near APOA1, APOA4, APOA5 and APOC3, rs2108622 in CYP4F2 as well as rs11057830 in SCARB1.…”
Section: Genetic Polymorphismsmentioning
confidence: 99%
“…At entry (n 212) and at the end of the 3-month period (n 169), biochemical analyses were performed as previously described (10,11) . For polymorphism detection, genomic DNA were prepared from white blood cells isolated from whole blood samples by a standard proteinase K-phenol method as reported (12,13) . The polymorphisms were genotyped by a PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) assay.…”
Section: Snp-diet Interactions In the Medi-rivage Studymentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Scavenger receptor class B type 1 (SR-B1) might be a major receptor in the facilitated diffusion in Caco-2 cells, considering the results of studies using their antibodies and siRNAs. 22,25) In SR-B1 knockout mice, the efficiency of -carotene absorption was remarkably reduced, though not fully inhibited.…”
mentioning
confidence: 99%